Cognitive rehabilitation of patients with perceptive disorders surviving to ischemic ictus - Marcia Sandra Hernández Zayas; Laritza Zurita Mera; Elizabeth Lobaina Suarez; Isabel Adela Vigil Zulueta (Centro Provincial de Información de Ciencias Médicas, 2017)
A therapeutic intervention in 30 patients with motor deficit (hemiplegia/hemiparesis), surviving the ischemic ictus, irrigated by the mean cerebral artery with perceptive disorders (sensorial or atentional negligence or anosognosia), assisted in the Rehabilitation Department of "Dr. Juan Bruno Zayas Alfonso" Teaching General Hospital, was carried out in Santiago de Cuba, from January to November, 2016, aimed at evaluating the effectiveness of the rehabilitative treatment. The sample was divided in 2 groups of 15 members each: those of the control group received conventional treatment; those of the study group, conventional treatment and occupational therapy associated with cognitive rehabilitation. They were considered sociodemographic parameters, of clinical and functional valuation, as well as of global functional recovery. Heminegligence was the most frequent perceptive disorder (63.4%) and the study group showed a better functional recovery (93.3%) when concluding the treatment, reason why the effectiveness of the conventional rehabilitation integrated to cognitive techniques and occupational therapy was demonstrated.